Sugarcane tolerance to ratoon eradication with glyphosate determined by physiological responses - Silva, Marcelo de Almeida [UNESP]; Arantes, Marcel Tomas [UNESP]; Oliver, Rodrigo [UNESP]; Brunelli, Marcela Cristina [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2014)
This study aimed to evaluate the tolerance of sugarcane cultivars to ratoon eradication under different glyphosate rates by means of physiological responses. Therefore, a trial was carried out in randomized complete blocks with 4 x 4 factorial design (cultivars x rates) totaling 16 treatments with four replicates. The cultivars IAC91-5155, IACSP93-3046, and IAC86-2480 and IAC87-3396 and the glyphosate rates 0 g ha-1; 1,920 g ha-1; 2,400 g ha-1; 2,880 g ha-1 were tested. The variables analyzed were percentage of tiller mortality, quantum efficiency of PSII (Fv/Fm) and SPAD index. The results showed that there are differences among sugarcane cultivars for tiller eradication and for physiological responses with glyphosate different rates. The rate of 2,880 g ha-1 was the most efficient in eliminating sugarcane tillers. The cultivars IAC86-2480, IAC87-3396 and IACSP93-3046 were the most sensitive and the IAC91-5155 tolerated, for a longer period of time, the damage to the photosynthetic apparatus of the ratoons caused by glyphosate desiccation. Due to different responses, different managements should be considered for eliminating ratoons of different cultivars.

O presente trabalho teve como objetivo avaliar a tolerância de cultivares de cana-de-açúcar à erradicação de soqueiras com diferentes doses de glyphosate por meio de respostas fisiológicas. Para isso, um ensaio foi desenvolvido no delineamento experimental de blocos ao acaso em esquema fatorial 4 x 4 (cultivares x doses), totalizando 16 tratamentos com quatro repetições. Foram utilizados os cultivares IAC91-5155, IACSP93-3046, IAC86-2480 e IAC87-3396 tratados com as doses de glyphosate 0, 1.920, 2.400, e 2.880gha-1. As variáveis analisadas foram porcentagem de perfilhos mortos, eficiência quântica do FSII (Fv/Fm) e índice SPAD. Há diferenças entre cultivares de cana-de-açúcar quanto à eliminação de perfilhos e a respostas fisiológicas a diferentes doses de glyphosate. A dose de 2.880gha-1 foi a mais eficiente em eliminar perfilhos de cana-de-açúcar. Os cultivares IAC86-2480, IAC87-3396 e IACSP93-3046 foram os mais sensíveis, e o IAC91-5155 tolerou por mais tempo os danos promovidos no aparato fotossintético à dessecação das soqueiras pelo glyphosate. Devido às respostas diferenciadas, manejos distintos devem ser considerados para a eliminação das soqueiras de diferentes cultivares.
Tolerância da soqueira da cana-de-açúcar à erradicação com glyphosate determinada por respostas fisiológicas
Keywords: Saccharum spp.; variedades; perfilhos; fluorescência da clorofila; SPAD; herbicida; Saccharum spp.; varieties; tillers; chlorophyll fluorescence; SPAD; herbicide